Perlindungan Hukum Terhadap Korban Kekerasan Seksual di Perguruan Tinggi Yang Ada di Kota Kupang - Melinda Dewanda Megalini Pekuwali; Karolus K. Medan; Renny Rebeka Masu (Syntax Idea)
Sexual violence within higher education institutions is a critical issue requiring focused attention. This study aims to analyze the forms of legal protection provided to victims and the measures of law enforcement taken against perpetrators of sexual violence in Kupang City. The research employs a normative and empirical approach using primary and secondary data. The findings indicate that legal protection for victims includes restitution, legal assistance, confidentiality assurance, and psychological support. Furthermore, universities enforce penalties against perpetrators through administrative sanctions, written apologies, and suspension. However, not all universities have comprehensive internal regulations to address sexual violence cases. Therefore, it is recommended that higher education institutions establish a Task Force for the Prevention and Handling of Sexual Violence and formulate rector regulations aligned with Ministerial Regulation No. 30 of 2021. These efforts are expected to foster a safe and violence-free campus environment.